(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This study investigates the determinants of artificial intelligence (AI) usability in the Irish medical system using a balanced panel dataset of 30 hospitals from 2015 to 2025. Employing fixed-effects and random-effects estimations with cluster-robust standard errors, the research examines how digital investment, staff training, patient digital engagement, and infrastructure readiness influence AI usability. Results reveal that staff training and patient engagement are the strongest predictors of usability, while infrastructure and investment exert weaker effects when human-centred variables are included. These findings underscore the importance of organisational readiness and user-centric strategies in ensuring effective AI adoption in healthcare. The study contributes to the growing empirical literature on digital transformation in health services by providing evidence from Ireland’s evolving health-technology landscape. Policy implications include prioritising workforce digital literacy and patient-focused innovation to enhance system-wide usability and ensure equitable AI integration across hospitals.